![image](https://tex.z-dn.net/?f=+x%5E%7B4%7D%2B+y%5E%7B4%7D%2B8+%5Cgeq+8xy+%0A%5C%5C%5C%0A+x%5E4%2By%5E4%2B8-8xy%3Dx%5E4%2B2x%5E2y%5E2%2By%5E4-2x%5E2y%5E2-8xy%2B8%3D%0A%5C%5C%5C%0A%3D%28x%5E2%2By%5E2%29%5E2-2%28x%5E2y%5E2%2B4xy-4%29%3D%0A%5C%5C%5C%0A%3D%28x%5E2%2By%5E2%29%5E2-2%28x%5E2y%5E2%2B4xy%2B4-4-4%29%3D%0A%5C%5C%5C%0A%3D%28x%5E2%2By%5E2%29%5E2-2%28%28xy%2B2%29%5E2-8%29%3D%0A%5C%5C%5C%0A%3D%28x%5E2%2By%5E2%29%5E2-2%28xy%2B2%29%5E2%2B16+%3E+0)
0" alt=" x^{4}+ y^{4}+8 \geq 8xy
\\\
x^4+y^4+8-8xy=x^4+2x^2y^2+y^4-2x^2y^2-8xy+8=
\\\
=(x^2+y^2)^2-2(x^2y^2+4xy-4)=
\\\
=(x^2+y^2)^2-2(x^2y^2+4xy+4-4-4)=
\\\
=(x^2+y^2)^2-2((xy+2)^2-8)=
\\\
=(x^2+y^2)^2-2(xy+2)^2+16 > 0" align="absmiddle" class="latex-formula">
Так как последнее выражение верно, то и исходное неравенство верно.